Melatonin Decreases Negative Effects of Combined Drought and High Temperature Stresses through Enhanced Antioxidant Defense System in Tomato Leaves - Mumithra Kamatchi K. Annadurai; Senthil Alagarsamy; Kalarani M. Karuppasami; Swarnapriya Ramakrishnan; Marimuthu Subramanian; Prasad R. B. Venugopal; Raveendran Muthurajan; Geethalakshmi Vellingiri; Vijayalakshmi Dhashnamurthi; Ravichandran Veerasamy; Boominathan Parasuraman; Sivakumar Rathinavelu; et al. (Horticulturae, 2023)
In tomato (Lycopersicon esculentum L.), the effects of combined drought (D) and high temperature (HT) stress during the flowering stage had not been studied in detail. Therefore, this study was conducted with an objective of quantifying the effects of foliar spray of melatonin under individual and combined drought and HT stress. At flowering stage, D stress was imposed through withholding irrigation, while HT stress was imposed through exposing the plants to ambient temperature (AT) along with an increase of +5 °C. Under D + HT, plants were first subjected to drought followed by a + 5 °C increase in AT. The duration of individual or combined stress was ten days. At 80% available soil moisture, 100 µM melatonin was sprayed on D, HT, or D + HT treated plants. Among the stresses, D + HT stress increased the thylakoid membrane damage and decreased the photosynthetic rate and fruit yield more than D or HT stress. Foliar spray of 100 µM melatonin produced decreased thylakoid membrane damage [D: 31%, HT: 26%, and D + HT: 18%] and increased antioxidant enzyme, viz., superoxide dismutase, catalase, peroxidase, ascorbate peroxidase, and glutathione reductase, activity over stress-control plants. The photosynthetic rate [D: 24%, HT: 22%, and D + HT: 19%] and fruit yield [D: 32%, HT: 23%, and D + HT: 16%] were increased over stress-control plants. Hence, it is evident that the increased photosynthetic rate and fruit yield in D + HT and 100 µM melatonin-sprayed plants may be associated with an increased antioxidant defense system. Melatonin as a novel biostimulator has a great potential in scavenging free radicals through increased antioxidant activity, which shields the photosynthetic membrane from damage and therefore helps in stress mitigation.